Fragile X-Associated Diminished Ovarian Reserve and Primary Ovarian Insufficiency from Molecular Mechanisms to Clinical Manifestations - Man, Limor; Lekovich, Jovana; Rosenwaks, Zev; Gerhardt, Jeannine (Frontiers in Molecular Neuroscience, 2017)
Fragile X syndrome (FXS), is caused by a loss-of-function mutation in the FMR1 gene located on the X-chromosome, which leads to the most common cause of inherited mental retardation in males and the leading single-gene defect associated with autism. A full mutation (FM) is represented by more than 200 CGG repeats within the FMR1 gene, resulting in FXS. A FM is inherited from women carrying a FM or a premutation (PM) (55-200 CGG repeats) allele. PM is associated with phenotypes distinct from those associated with FM. Some manifestations of the PM are unique; fragile-X-associated tremor/ataxia syndrome (FXTAS), and fragile-X-associated primary ovarian insufficiency (FXPOI), while others tend to be non-specific such as intellectual disability. In addition, women carrying a PM may suffer from subfertility or infertility. There is a need to elucidate whether the impairment of ovarian function found in PM carriers arises during the primordial germ cell development stage, or due to a rapidly diminishing oocyte pool throughout life or even both. Due to the possibility of expansion into a FM in the next generation, and other ramifications, carrying a PM can have an enormous impact on one’s life; therefore, preconception counseling for couples carrying the PM is of paramount importance. In this review, we will elaborate on the clinical manifestations in female PM carriers and propose the definition of FXDOR, then we will review recent scientific findings regarding possible mechanisms leading to FXDOR and FXPOI. Lastly, we will discuss counseling, preventative measures, and interventions available for women carrying a PM regarding different aspects of their reproductive life, fertility treatment, pregnancy, prenatal testing, contraception, and fertility preservation options.